Bima ethnic medicinal plants as a natural hand sanitizer - Mahrun Mahrun; Mujiono Sang Putra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to identify potential ethnic plants with medicinal properties in Bima Regency, Indonesia, as hand sanitizers. The type of research is experimental research, with a completely randomized design with two factorials: concentration of medicinal plant extracts and the ratio of alcohol and triclosan. The medicinal plants used are cherry, meniran (Phyllanthus Urinaria), the burden of straw, ketepeng (Senna alata), white turmeric, and guava, taken from the leaves. The results showed that the test plant extracts (cherry, meniran, pandanus, ketepeng, white turmeric, and guava) all had inhibitory power based on the test concentration. The ability of the inhibition of bacteria in the test plant extracts had different diameters of inhibition, where the average concentration of each concentration that had the lowest diameter of inhibition could be seen in the plant extract. In contrast, in the plant extract treatment, the inhibition zone began to appear at a concentration of 20%. In other treatments with other test plant extracts, a zone of the inhibition began to form at a concentration of 10%. Meanwhile, the plant extract which has the largest relative inhibition zone is the white turmeric plant extract. Tests on each test, namely cherry, meniran, ketepeng, white turmeric, and guava, used a concentration of 10%, and the burden of straw used an extract concentration of 20%. The overall hand sanitizer shows characteristics in the treatment concentration A1 = 4% and the concentration of alcohol and triclosan B2 = 1 ml: 1.5 g.pH of the hand sanitizer for various plants was obtained in a relatively similar pH range, namely in the range of 6.06 - 6.82.